2022
DOI: 10.1186/s12905-022-01832-9
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of square dance on musculoskeletal system in early postmenopausal Chinese women: a cross-sectional study

Abstract: Background This study was set to investigate the correlation between square dance and musculoskeletal system of early postmenopausal Chinese women. Methods Chinese postmenopausal women, who had been without menstruation for 1–10 years from the onset of menopause were recruited from community centers for this study. A standardized structured face-to-face interview was performed to collect demographic information, life styles, personal medical histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Most of our surveys began after the COVID-19 pandemic, so the number of people gathering for square dancing may have decreased. However, our preliminary findings suggested that square dancing, which was beneficial for the musculoskeletal system [ 30 ] and incorporated the pleasurable experience of social communication [ 31 ] and musical rhythm [ 32 ], may provide greater cognitive protection with less time spent exercising and thus could be regarded as a recommended method of LTPA for elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our surveys began after the COVID-19 pandemic, so the number of people gathering for square dancing may have decreased. However, our preliminary findings suggested that square dancing, which was beneficial for the musculoskeletal system [ 30 ] and incorporated the pleasurable experience of social communication [ 31 ] and musical rhythm [ 32 ], may provide greater cognitive protection with less time spent exercising and thus could be regarded as a recommended method of LTPA for elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Following a gluten-free diet that's rich in calcium and vitamin D can help maintain healthy bones. 11 Physical exercises, including dancing, have multiple benefits on muscle strengthening and bone loss prevention. 11 It's recommended by the Bone Health and Osteoporosis Foundation that weightbearing exercises be done for 30 minutes on most days of the week, done at one time, or spread out throughout the day.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quattrini and colleagues state that “consumption of food groups typical of the Mediterranean diet, such as fruit, vegetables, low-fat dairy products, and fish, is essential for maintaining good bone health.” Celiac disease causes malabsorption of calcium, vitamin D, and other proteins and nutrients, which can lead to osteoporosis. Following a gluten-free diet that's rich in calcium and vitamin D can help maintain healthy bones 11…”
Section: Literature Reviewmentioning
confidence: 99%
“…13 In addition, physical activity helps improve bone mineral density, muscular strength, and body balance in postmenopausal women. 14 Exercise has also been shown to improve vascular health, 15 reduce arterial stiffness, 16 improve subjective wellbeing, 17 and quality of life. 18 Physical activity is defined as any bodily movement produced by skeletal muscles requiring energy expenditure.…”
mentioning
confidence: 99%
“…High levels of physical activity have been associated with fewer depressive symptoms during menopausal transition, 12 which is important because women are more susceptible to the development of depression during this time 13 . In addition, physical activity helps improve bone mineral density, muscular strength, and body balance in postmenopausal women 14 . Exercise has also been shown to improve vascular health, 15 reduce arterial stiffness, 16 improve subjective well-being, 17 and quality of life 18 …”
mentioning
confidence: 99%